GAMBARAN KEBUTUHAN SPIRITUAL PADA LANSIA YANG BERAGAMA ISLAM DI DESA SRATUREJO KECAMATAN BAURENO KABUPATEN BOJONEGORO TAHUN 2014 - RAHMAWATI, RAHMAWATI; SYA'DIYAH, SITI NURUL; Praja Santika, Eka wahyu (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2015)
ABSTRACT Spiritual needs of the religion of Islam is to implement the pillars of Islam is Shahadah, establish prayer, pay the obligatory charity, fasting and departing do Hajj. Purpose of this study was to determine the description of the spiritual needs of the elderly Moslem.Descriptive research design with a survey approach, a population of 359 people, samples of 97 respondents, sampling Quota sampling technique. Single variable, namely the spiritual needs of the elderly who are Islamic . Methods of data collection using questionnaire guided interviews and then conducted data processing by means of editing, coding, scoring, tabulating and analyzed the data using descriptive.The results of this study are more than most of his spiritual needs met as many as 56 respondents (57.73 %) and less than most of their spiritual needs are not met as many as 38 respondents (39.18 %)More than most of his spiritual needs are met . It is expected that this study can make the elderly may be more active in worship to God Almighty and to unmet needs in order to obtain his spiritual guidance in order to fulfill their obligations be fulfilled spritual. Keywords : Elderly , spiritual needs , elderly Moslem